The Impact of Nasalance on Cepstral Peak Prominence and Harmonics‐to‐Noise Ratio. (25th December 2018) - Madill, Catherine; Nguyen, Duong Duy; Yick‐Ning Cham, Kristie; Novakovic, Daniel; McCabe, Patricia
Abstract : Objectives/Hypothesis: Cepstral peak prominence (CPP) has been reported as a reliable measure of dysphonia and a preferred alternative to harmonics‐to‐noise ratio (HNR). However, CPP has been observed to be sensitive to articulatory variation and vocal intensity. The aim of this study was to examine the impact of nasalance on CPP and HNR of voice signals. It was hypothesized that increased nasalance would be associated with decreased CPP. Study Design: Within‐subject correlation design. Methods: Thirty vocally healthy female participants were recorded reading and producing a vowel in alternation with a nasal consonant while wearing a nasometer for calculation of nasalance. Recorded vowel, nasalized, and nasal segments of speech were used to calculate CPP using Analysis of Dysphonia in Speech and Voice software, and HNR and vocal intensity using Praat software. Results: Significant main effects of conditions were observed for CPP. CPP values decreased significantly when phonation changed from vowel to nasalized vowel and to nasal. There was correlation between CPP and nasalance and between CPP and intensity. HNR was slightly higher in the nasal condition than in vowel. There was a weak correlation between HNR and nasalance. No correlation was found between HNR and intensity. Conclusions: CPP is sensitive to changes in vocal tract configuration caused by nasalization as well as intensity, whereas HNR is not. Therefore, CPP may reflect the periodicity in source signal or the filtering effects of vocal tract. Further research is needed to clarify the application and interpretation of CPP in clinical practice. Level of Evidence: 4 Laryngoscope, 129:E299–E304, 2019